Toward a smarter, sustainable and satisfying life: Exploring the mechanism of smart rural tourism construction empowering rural revitalization in the area of Yangtze River Delta - Sheling Ye; Lei Shi; Zhen Feng; Gwon Hyuk (Heliyon)
In China's developed regions such as the Yangtze River Delta, Rural revitalization is no longer about poverty alleviation, but aims to build a modern country. Previous studies have confirmed the important role of tourism in rural development, but there is a lack of studies discussing the dimensions of smart rural tourism construction and how it empowers a higher level of rural revitalization, which provides a possibility for the application of smart tourism construction in more developed rural areas to achieve a higher level of rural revitalization. Therefore, this study aims to explore how smart rural tourism construction empowering rural revitalization in the developed rural areas in China. Building upon this, the study focused on the Xuelang area of Wuxi City, Jiangsu Province as the research case. This area has abundant rural tourism resources and technological industries, representing a typical relatively developed rural area in the Yangtze River Delta region. The study interviewed 36 people, who are from local tourism government sectors, tourism businesses, and local villagers. Through the grounded theory method, this study has explored six main categories: Macro Factors, Driving Force, Internal Force, External Force, Empowering Performance, and Ultimate Goals. A theoretical mechanism for smart rural tourism construction empowering rural revitalization was developed with the core category of rural revitalization. This study enriches the research scope of smart tourism destinations, the dimensions of smart rural tourism construction, and reveals the empowering mechanism between these dimensions and rural revitalization in developed rural areas.